Treatment and risk factor analysis of hypoglycemia in diabetic rhesus monkeys - He, S.; Chen, Younan; Wei, L.; Jin, X.; Zeng, L.; Ren, Y.; Zhang, J.; Wang, L.; Li, H.; Lu, Y.; Cheng, J. (2011)
In order to anticipate and promptly treat hypoglycemia in diabetic monkeys treated with insulin or other glucose-lowering drugs, the relationships between the incidence and symptoms of hypoglycemia in these animals, and many factors involved in model development and sustainment were analyzed. Different procedures were performed on 22 monkeys for the induction of diabetes. The monkey models were evaluated by blood glucose, insulin, C-peptide levels and intravenous glucose tolerance tests. A glucose treatment program for the diabetic monkeys was administered and laboratory tests were regularly performed. A standard procedure of hypoglycemia treatment was established and the risk factors of hypoglycemia were analyzed by a logistic regression model. Furthermore, the relationships between the four methods of diabetes induction, renal function, glycemic control and hypoglycemia were studied using one-way analysis of variance and t-test. We found that the hypoglycemic conditions of diabetic monkeys were improved rapidly by our treatment. The statistical analysis suggested that the modeling methods, renal function and glycemic control were related to the incidence of hypoglycemia. In detail, the progress of diabetes, effects of glycemic control and, particularly, the severity of the hypoglycemia differed according to the induction strategy used. The models induced by partial pancreatectomy with low-dose streptozotocin were not prone to hypoglycemia and their glycemic controls were stable. However, the models induced by total pancreatectomy were more vulnerable to severe hypoglycemia and their glycemic controls were the most unstable. Moreover, the levels of blood creatinine and triglyceride increased after the development of diabetes, which was related to the occurrence of hypoglycemia. In conclusion, we suggested that total pancreatectomy and renal impairment are two important risk factors for hypoglycemia in diabetic monkeys. More attention should be paid to daily care of diabetic monkeys, particularly monitoring and protecting their renal function. Copyright © 2011 by the Society for Experimental Biology and Medicine.